(untitled) (TULSSAA Journal, 2025)
Citing sources precisely according to the American Psychological Association (APA) 7th edition guidelines poses challenges for many writers. This review article systematically examines the primary types and subtypes of in-text citations outlined in the APA 7th edition, focusing on their patterns and practical usage. Through a thematic analysis of the ‘Publication Manual of the American Psychological Association: The Official Guide to APA Style,’ with the aid of ATLAS.ti software, we identified fundamental principles of citation and categorized citation types. The findings are presented thematically, including fundamental principles for in-text citation, detailed classifications of citation types, and illustrative examples. The discussion integrates insights from the extant literature, offering guidance on embedding citations into academic writing. The study emphasizes the APA 7th edition’s comprehensive framework for in-text citations while noting the dispersed nature of this information within the manual. This article serves as a practical resource for writers seeking clarity on APA-style citations, facilitating their proper and effective use in scholarly work.